Exploring YouTube Marketing Communication: Brand awareness, brand image and purchase intention in the millennial generation - Mohamad Trio Febriyantoro (Cogent Business & Management, 2020)
Companies can use digital media in promoting their business or social media like Facebook, Instagram, YouTube. Many researchers examine the effects of different uses of social media on consumer buying behavior from different perspectives. The purpose of this research is to see the application of YouTube Ads in building brand awareness and brand image and its effect on purchase intention. Respondents in this study are millennials who are in Batam City and surrounding areas with an age range of 18–35 years chosen using the non-probability sampling method. This study uses Structural Equation Modeling (SEM) with the SmartPLS. YouTube Advertising influences brand awareness and brand image, whereas brand awareness and brand image do not affect purchase intention. YouTube ads are directly related to the purchase intention. Brand awareness and brand image are not mediating variables because they are not associated with purchase intention.